"Sarcophagus in nenfro (called of the Poet) with different scenes
Front: Atridal saga scenes, Clytemnestra is lying on the altar, killed by her son Orestes, to avenge the murder of father Agamemnon; at the right, Orestes and Pylades are near the body of Egistus, Clytemnestra's lover; Electra is seated near the altar; at the left, Orestes is being persecuted by the Erinys. Back: Theban saga scenes, a dual between Eteocles and Polynices observed by funerary demons holding flares; the seated Jocasta contemplating suicide and the blind Oedipus. On the sides: Telephus in the Greek camp threatening to kill the young Orestes; Neoptolemeus sacrificing Polyxena on the tomb of Achilles? The lid (which does not actually belong to the sarcophagus) represents the deceased reclining, holding a book-scroll.